In Silico approach for the preliminary analysis of the allergenicty of globulin 11S in pili nuts (canarium ovatum) - Libuit, Aaron Joseph C. (College of Home Home Economics, University of the Philippines Diliman, 2023)
This study aimed to utilize in-silico methods in assessing the allergenicity of globulin 11S in Pili nuts (Canarium ovatum). A total of 12 Pili nut protein sequences were collected from both the UniProt and NCBI protein databases. Allermatch and AlgPred were utilized to determine the allergenicity of the proteins collected. Based on the Allermatch screening, six Pili nut protein sequences (atpB, high MW oleosin isoform 1, high MW oleosin isoform 2, small heat shock protein, GAPDH, and globulin 11S) were considered as potential allergen due to having greater than 35% sequence similarity to known allergens in the Allermatch database. Globulin 11S was determined to be the most allergenic among these six Pili nut proteins as it has a hit/match of over 50% sequence identity to 13 known allergens. Based on the AlgPred screening, five Pili nut protein sequences (high MW oleosin isoform 1, high MW oleosin isoform 2, small heat shock protein, GAPDH, and globulin 11S) were considered as potential allergens due to being positive to at least one of the predictive approaches of AlgPred. Globulin 11S was determined to be the most allergenic among these five Pili nut proteins based on consensus prediction. Comparing the results of the Allermatch and AlgPred, it was observed that atpB is considered as an allergen in Allermatch screening only and is not considered as an allergen by AlgPred suggesting that the Allermatch result for atpB of Pili nuts might be a false positive result. Also, it was observed that Globulin 11S was considered to be the most allergenic in both screening methods. The findings in this study can contribute to the knowledge pool to better understand the allergenicity of Pili nuts.